VD_FINDINFO HC / 2014 / 898 vom 21. Oktober 2014 - VD Tribunal cantonal (2014)
CONTRAT D'ENGAGEMENT DES VOYAGEURS DE COMMERCE, PROVISIONCOMMISSION, FRAIS PROFESSIONNELS | 327a al. 1 CO, 327b al. 1 CO, 337 CO, 337c CO, 347 al. 1 CO, 355 CO